2012
DOI: 10.2174/2210686311202020096
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analysis and Non Linear Dynamics Applied to Voice Pathology Detection: A Review

Abstract: A complete review of scientific studies and relevant patents oriented to voice pathology detection is presented in order to provide a good and quick reference for readers who want to understand how the field of automatic detection of voice disorders has evolved. Referenced works are divided into three groups, one focused on classical Acoustic Analysis of Voice (AAV), second on Non Linear Dynamics (NLD) and third on different and relevant patents presented in the development of systems for the automatic evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Some research works demonstrated that pitch, formants and NHR, HHR, GNR etc. can represent some characteristics of the pathological voice such as hoarseness, breathiness and roughness [12,13], which can all be seen on spectrograms. In STFT, each file use 10 ms hamming window segments, with 50% overlap between consecutive windows.…”
Section: B Pre-processing For Input Data To Cnnmentioning
confidence: 99%
“…Some research works demonstrated that pitch, formants and NHR, HHR, GNR etc. can represent some characteristics of the pathological voice such as hoarseness, breathiness and roughness [12,13], which can all be seen on spectrograms. In STFT, each file use 10 ms hamming window segments, with 50% overlap between consecutive windows.…”
Section: B Pre-processing For Input Data To Cnnmentioning
confidence: 99%
“…One of them is by looking for new meaningful features, using a well known classifier. In that regard multiple research lines have been proposed, from pitch related features [5], cepstral analysis [6]- [8], non-linear analysis [9], [10] or wavelet transformation [11]. Other common route is researching a good new classifier which improves the already known ones, since new machine learning techniques are being constantly researched, and many of them have been applied to this particular field using already known features [12].…”
Section: Introductionmentioning
confidence: 99%
“…This family of methods aims to measure the atypical acoustic resonance resulting from VPD as an objective proxy for hypernasal speech. Previous work in this area can be categorized broadly in two groups: engineered features based on statistical signal processing [20] and supervised methods based on machine learning [21]. The simple acoustic features fail to capture the complex manifestation of hypernasality in speech, as there is a great deal of person-to-person variability [22].…”
Section: Introductionmentioning
confidence: 99%